(3cJGH aj SjQI GdfHj Udi Gddg Ydjg hSdes
(3ChdgG (B:s
(3eHJhQ GdChd, hChd GdehLhO efg(B: "(3hSde hdUbgG aGdUbJ , hCUjH MHjH GjVkG jhe HOQ HVQHI Ydi YGJbg MJi eGd Tbg aQOg QShd Gddg Udi Gddg Ydjg hSde hJad Ydjg MJi UM s
(3BNQgG (B:s
(3LeYJ gPg GdCMQa HGdbOS GdTQja , QGLjkG ef GdQH GddWja GdYah YeG CLJQMJg hVjYJ hbJj HGdJShja s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B340 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs